Experience with VariClose® vein sealing system in the Czech Republic. (March 2022) - Balaz, Peter; Rokosny, Slavomir; Herman, Jiri; Pirkl, Miloslav; Vlachovsky, Robert; Whitley, Adam
Objectives: The aim of this study was to assess occlusion rates of saphenous veins treated with the VariClose vein sealing system. Methods: A retrospective analysis including a total of 64 patients from four centres from the Czech Republic. Occlusion was defined as a non-compressible vein with absence of flow with exception to the first 3 cm from the saphenofemoral or saphenopopliteal junction on duplex ultrasound. Results: In 64 patients a total of 79 veins were treated. Technical success of the procedure was achieved in 74 (94%) of cases. The mean follow-up was 5.5 months. The closure rates calculated by the Kaplan-Meier method at 1, 3, 6 and 12 months were 94%, 85%, 69% and 36%, respectively, and there were no significant differences between centers. The average difference in VCSS score before and after the procedure was 1.8. Conclusions: The present study demonstrated surprisingly worse occlusion rates than the current literature.